2022
DOI: 10.3390/cosmetics9010019
|View full text |Cite
|
Sign up to set email alerts
|

Food Loss and Food Waste for Green Cosmetics and Medical Devices for a Cleaner Planet

Abstract: To stay wealthy in a world where all can live in prosperity and wellbeing, it is necessary to develop sustainable growth at net zero emissions to stop climate change, neutralizing both risks and diseases such as the COVID-19 pandemic and inequalities. Changing the worldwide use of the great quantity of food loss and waste can help to move in this direction. At this purpose, it seems useful to transform food waste into richness, extracting and using its content in natural ingredients and biopolymers to make new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 106 publications
0
13
0
Order By: Relevance
“…Industrial plant-derived food waste could represent, for the cosmetic field, an important natural source of biodegradable, skin-friendly, and environmentally friendly ingredients, such as proteins, polysaccharides, lipids, fibers, vitamins, phytochemicals, and minerals, that can exert either functional or technical activities, including antioxidants, moisturizing, nourishing, antiwrinkle properties, thickening, stabilizing, etc. [158][159][160].…”
Section: Cosmetic Applicationmentioning
confidence: 99%
“…Industrial plant-derived food waste could represent, for the cosmetic field, an important natural source of biodegradable, skin-friendly, and environmentally friendly ingredients, such as proteins, polysaccharides, lipids, fibers, vitamins, phytochemicals, and minerals, that can exert either functional or technical activities, including antioxidants, moisturizing, nourishing, antiwrinkle properties, thickening, stabilizing, etc. [158][159][160].…”
Section: Cosmetic Applicationmentioning
confidence: 99%
“…However, this waste has a large potential to be used in the cosmetic industry as a raw material rich in antioxidants, polyphenols, proteins, minerals, vitamins, carotenoids, lignans, polysaccharides, natural-derived polymers, and other substances (Figure 1). Eliminating waste from the food industry and turning it into valuable products became a necessity to save natural resources and avoid methane and carbon dioxide emissions, thus helping to boost a circular economy [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that the amount of household food waste produced is as high as 60-110 kg/capita/year, according to world localization [7]. The extraction of valuable chemicals and raw materials from food waste has been widely exploited in the fields of packaging [8][9][10], cosmetics [11], pharmaceutics [12][13][14][15][16], and green electronics [17], and, recently, it has started to be extended to the field of environmental remediation [18].…”
Section: Introductionmentioning
confidence: 99%